Effect of Mirror Therapy on Phantom Pain Levels in Post Amputation Patient: a Literature Review - Jon Hafan Sutawardana; Siswoyo Siswoyo; Wantiyah Wantiyah; Fahruddin Kurdi; Murtaqib Murtaqib; Dwi Ayu Sari; Ana Nistiandani (Faculty of Nursing, Universitas Jember, 2022)
Background: Phantom pain after amputation is ordinary. Phantom pain is challenging to treat, so it will last a long time which will cause depression and anxiety and reduce the quality of life. There are various treatment options: pharmacological (antidepressants, anesthetics) and non-pharmacological (acupuncture, hypnosis). However, there is still no proven effective therapy, so it is necessary to try a non-pharmacological therapy that is safe, cheap, and easy, namely mirror therapy. Purpose: This study aims to determine how the effect of mirror therapy on the phantom pain of post-amputation patients. Methods: Narrative literature review of a publication registered 2017-2021 on Pubmed, ProQuest, EBSCO, and Google Scholar. Search articles using the keywords